Risk Mitigation Analysis of Fish Cracker Products Supply Chain Using House Of Risk Method Case Study: Sri Tanjung Cracker Company - Derma Fitriani; Asep Erik Nugraha (TALENTA Publisher, 2022)
The Sri Tanjung Cracker Company is an MSME that produces fish crackers. Currently, the Sri Tanjung cracker company lacks structured risk management, particularly in supply chain activities One of the known risks is that companies run out of raw materials, suppliers who ship late, and defective products. The goal of this study was to identify risks and develop appropriate preventive measures to reduce risks in the fish cracker production supply chain. This study maps supply chain operations using the SCOR model then uses the HOR method to classify risks and related mitigation strategies using Pareto diagrams and a probability impact matrix model. The results showed that the HOR phase 1 model comprises 60 risk events, 35 risk agents, and 7 priority risk agents for HOR phase 2 computation. HOR phase 2 shows 4 mitigation strategies that need to be addressed first. To conduct further research, if the suggested action is in the form of preventive action, it is required to quantify the impact of risk reduction and can add variables in the review of risk events, risk agents, and preventive measures to identify supply chain activities at the Sri Tanjung Fish Cracker Company.